Air Terjun Lider Sebagai Daya Tarik Wisata Alam Di Desa Sumber Arum, Kecamatan Songgon, Kabupaten Banyuwangi, Jawa Timur - Wilda Rifqi Mabrurin; I Made Adikampana (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2021)
Banyuwangi Regency has proved their strategy developed tourism sector as priority. Banyuwangi have many tourism potential, start with natural, cultural and artificial. One of natural tourist destination is Lider Waterfall at Songgon district. The natural beauty of the Lider waterfall attracts many tourists to get some pleasure and take many picture. This study aims to identify the potential tourist attraction of Lider Waterfall. This research used qualitative method with quantitative and qualitative type of data. Data collection technique by observation, interviews and study of documents. The data analysis used is descriptive-qualitative data analysis to describe tourist attraction components. The results of this study indicate that the condition of the tourist attraction that is reviewed through the tourist attraction component currently Lider Waterfall has the main attractions of waterfalls, horse riding, offroad jeeps, trail and bycycle. Accessibility to the waterfall is easy to reach, the facilities around the waterfall are adequate and managed by Pokdarwis. The point is the tourist attraction component at Lider Waterfall has been very well realized. Hence, sustainable maintain must be focus because tourism is not for now but more think about the future of nature and for the next generation. Keyword: watterfall lider, tourist attraction